2010
DOI: 10.1111/j.1365-3059.2010.02383.x
|View full text |Cite
|
Sign up to set email alerts
|

Multigene sequence data and genetic diversity among ‘Candidatus Phytoplasma ulmi’ strains infecting Ulmus spp. in Serbia

Abstract: Elm yellows phytoplasmas (EY) belonging to the 16SrV-A subgroup were recently proposed as a new candidate species 'Candidatus Phytoplasma ulmi'. These pathogens infect elm trees, causing leaf yellowing and premature drying. In this study, 25 isolates originating from localities in northeast, east and southwest Serbia were characterized by means of RFLP analysis and DNA sequencing of four genomic loci: 16S rRNA, ribosomal protein rpl22-rps3, secY and map. In total, five different genotypes were identified based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 26 publications
1
52
0
Order By: Relevance
“…Its identification has also been confirmed by multilocus sequence analysis (Arnaud et al, 2007;Jović et al, 2011 …”
Section: Taxonomymentioning
confidence: 92%
See 2 more Smart Citations
“…Its identification has also been confirmed by multilocus sequence analysis (Arnaud et al, 2007;Jović et al, 2011 …”
Section: Taxonomymentioning
confidence: 92%
“…Other phytoplasmas are found in other woody perennial hosts and cause diseases known as Alder yellows, flavescence dorée, rubus stunt, cherry lethal yellows or jujube witches' broom (Jović et al, 2011).…”
Section: Taxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…P. ziziphi" (the jujube witches' broom agent) by less than 2.5% in 16S rDNA sequence similarity, the threshold for assigning species rank to phytoplasmas under the provisional status "Candidatus" (IRPCM Phytoplasma/Spiroplasma Working Team -Phytoplasma taxonomy group, 2004). P. ulmi" strains infecting elm trees in Serbia and Croatia (Jović et al, 2011;Katanić et al, 2016), which differ from the "Ca. Nucleotide sequence comparisons revealed that four strains of "Ca.…”
Section: Taxonomic Positionmentioning
confidence: 96%
“…P. rubi" (the rubus stunt agent) and "Ca. However, typing of additional European strains based on RFLP and sequence analyses of 16S rRNA, rplV, rpsC, secY and map genes showed genetic diversity within this pathogen (Arnaud et al, 2007;Jović et al, 2008Jović et al, , 2011Katanić et al, 2016;Quaglino, Casati, Eccher, & Bianco, 2005). However, supporting data for separating the above taxa at the putative species level were obtained by examining other molecular markers and considering biological properties, such as host range and insect vector specificity (Jung et al, 2003;Lee et al, 2004;Malembic-Maher et al, 2011;Martini, Marcone, Lee, & Firrao, 2014).…”
Section: Taxonomic Positionmentioning
confidence: 99%